Ekstrak Daun Jati (Tectona grandis) Alternatif Pewarna pada Penghitungan Jumlah dan Viabilitas Sel Kultur Dibandingkan dengan Pewarna Tryphan Blue - I Gusti Ayu Sri Andayani; Sri Sulastri; Dwi Ampera Hananto; Made Sriasih (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Tryphan blue comes from toluidine which is one of the bases of toluene isomer which has a natural pigment content of anthsiasin. Tryphan blue is commonly used for cell counting and for the calculation of tissue viability in laboratory mice. Basically the use of tryphan blue is dangerous for laboratory workers because it has a carcinogenic effect, mutagenesis, so other materials are needed especially safer and harmless natural materials. This study aims to compare the quality of teak leaf dye extract as a natural dye on the calculation of the number and viability of culture cells compared to tryphan blue dye. The study used the Complete Randomized Design (RAL) method with three treatment factors (96% ethanol, 14% citric acid, and Phospat Buffer Saline (PBS)) and observations of 5 replays be used for the calculation of the number and viability of spleen cells in the 1st, 10th, 20th, and 30th minutes with tryphan blue as a positive control. The results showed that the quality of teak leaf dye with ethanol solvent 96% viability does not differ materially, provides good color quality and obtained the same viability time as tryphan blue.